Análise da influência de metal de adição de gás de proteção em juntas soldadas de aço galvanizado - Fensterseifer, Ricardo Augusto (2024)
The wide adoption of galvanized steel in the industrial segment, such as the automotive industry, is based on excellent properties in providing durability to manufactured products, in addition to reducing environmental impacts and costs in the production chain, avoiding corrosion and providing longer useful life due to protective zinc layer. However, this layer when subjected to the welding process involves potential defects due to zinc evaporation and fragility of the liquid metal during welding, with potential generation of porosity, lack of penetration or fusion. These defects can have significant impacts on the reduction of mechanical properties, cracks and fractures in welded joints. In this work, these implications are analyzed through the microstructural characteristics and mechanical properties of joints welded with ZAR230 galvanized steel by the GMAW and FCAW welding processes, evaluating factors that are most widely modified on an industrial scale in this welding technique: the type of filler metal , being solid wire or tubular - self-protected with gas shielding and without gas shielding, and the type of shielding gas (with mixtures of 92% Ar + 8% CO2, 80% Air + 20% CO2 and 95% Ar + 5% O2). Using techniques such as scanning optical microscopy, metallography, tensile tests, microhardness and defects, inclusions and bead appearance, the best combination being the use of solid wire with a mixture of 92% Ar + 8% CO2 because it presents fewer defects and better mechanical properties.